Electromagnetic waves diffraction a system of open cones in time domain - Doroshenko, V. A.; Artjukh, A. V.; Parhomenko, V. A. (IEEE, 2010)
A model problem of electromagnetic waves diffraction on an equalperiodical multilayered perfectly conducting conical grating is considered. The solution method is based on using the Meler-Fock integral transforms and the method of the coupling problem. This allows both analytical and numerical solutions obtaining.
Keywords: Meler-Fock integral transforms; analytical and numerical solutions